2014
DOI: 10.1186/1476-0711-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Study of the frequency of Clostridium difficile tcdA, tcdB, cdtA and cdtB genes in feces of Calves in south west of Iran

Abstract: BackgroundClostridium difficile (C. difficile) is a gram-positive, toxin-producing bacillus which is an intestinal pathogen in both humans and animals and causes a range of digestive disorders including inflammation of the bowel, abdominal pain, fever and diarrhea. C. difficile toxins include enterotoxin (Toxin A), cytotoxin (Toxin B) and a binary toxin. Two large protein toxins A and B are encoded by separate genes, tcdA and tcdB. Clostridium difficile infection (CDI) mainly caused by the activity of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…During a hospital outbreak of CDI in Pittsburgh, USA, up to 65 % of the clinically recovered C. difficile isolates had binary toxin genes (McEllistrem et al, 2005). Doosti & Mokhtari-Farsani (2014) reported that only 1.1 % of the C. difficile isolated from calves contained all four toxin genes, namely tcdA, tcdB, cdtA and cdtB. Recently, Eckert et al (2015) documented that C. difficile isolates producing only binary toxin were pathogenic despite the lack of TcdA and TcdB.…”
Section: Discussionmentioning
confidence: 99%
“…During a hospital outbreak of CDI in Pittsburgh, USA, up to 65 % of the clinically recovered C. difficile isolates had binary toxin genes (McEllistrem et al, 2005). Doosti & Mokhtari-Farsani (2014) reported that only 1.1 % of the C. difficile isolated from calves contained all four toxin genes, namely tcdA, tcdB, cdtA and cdtB. Recently, Eckert et al (2015) documented that C. difficile isolates producing only binary toxin were pathogenic despite the lack of TcdA and TcdB.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium difficile is a gram-positive toxin-producing bacillus that causes intestinal infections in humans and animals ( 1 ). C. difficile presents an emerging threat in hospital environments ( 2 ), causing a range of digestive disorders, including inflammation of the bowel, abdominal pain, fever and diarrhea ( 1 ). C. difficile infection has increased in prevalence and severity over the last decade ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of swine, the reported prevalence of C. difficile in cattle can vary wildly from one study to another depending on the geographical location studied, with percentages as diverse as 0 % in farms in North America and 60 % in Iran (Doosti and Mokhtari-Farsani 2014;McNamara et al 2011) (Table 2). Furthermore, the pathogenicity of C. difficile in cattle is not fully understood.…”
Section: Food-producing Animals: Cattlementioning
confidence: 99%